(untitled) (Research, Society and Development, 2021)
The current agricultural exploitation model is leading to the destruction of forest cover and soil degradation, however, the impacts are not limited to cutting-edge models, as family farming has its share, although less. In view of this, the propositions of Law No. 12,651 / 2012 and Law No. 9,974 / 2000, which deal with environmental issues and pesticides, respectively. We sought to identify the level of knowledge of family farmers who live in the municipality of Vitorino Freire, located in the state of Maranhão on such laws. The survey was applied directly by visiting the producers through a questionnaire that contained seventeen questions. Ten producers were interviewed in the months of January and February 2021. Most of the producers interviewed were male (80%), and 90% said they had no knowledge of Law No. 12,651 / 2012. And only 30% said they knew the danger level of a pesticide according to the color of its stripe. Therefore, it is noted that these producers are in need of information on such matters, which may be a consequence of a lack of technical assistance.